The Expressing Patterns of Opioid Peptides, Anti-opioid Peptides and Their Receptors in the Central Nervous System Are Involved in Electroacupuncture Tolerance in Goats - Wan, Juan; Qiu, Zhengying; Ding, Yi; Nan, Sha; Ding, Mingxing (Frontiers in Neuroscience, 2018)
To investigate dynamic processes of enkephalin (ENK), cholecystokinin octapeptide (CCK-8), orphanin FQ (OFQ) and their receptors (µ opioid receptor, MOR; CCK B type receptor, CCKBR and opioid receptor-like 1 receptor, OPRL1) in the central nerve system during electroacupuncture (EA) tolerance, EA of Sixty Hz was used to stimulate goats for 6 h. Pain threshold was measured using potassium iontophoresis. The expression levels of ENK, CCK-8 and OFQ and their receptors were determined with ELISA and qPCR, respectively. The results showed that the change rates of pain threshold in EA-treated goats decreased from 89.9 ± 11.7% at 0.5 h to –11.4 ± 8.9% at 6 h. EA induced the decreased ENK and increased CCK-8 and OFQ in the most measured nuclei. EA caused decreased preproenkephalin mRNAs in ACB, CAU, PVH and PAG at 4 h, and decreased or unchanged MOR mRNAs at 2 to 6 h, but increased CCK mRNAs in CAU, PVT, PVH, PAG and SCD at 4 to 12 h. Increased prepronociceptin mRNAs and fluctuated CCKBR and OPLR1 mRNAs were found in the most measured nuclei. ENK levels were positively correlated (p < 0.01) with the change rates of pain thresholds in the measured nuclei or areas while CCK-8 levels (or OFQ levels) were negatively correlated (p < 0.01) with the pain thresholds in CAU (or CAU and ACB). These results suggest that the development and recovery of EA tolerance may be associated with the specific expression patterns of opioid peptides, anti-opioid peptides and their receptors in the analgesia-related nuclei or areas.